2008
DOI: 10.1016/j.febslet.2008.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Glucose‐induced production of hydrogen sulfide may protect the pancreatic beta‐cells from apoptotic cell death by high glucose

Abstract: a b s t r a c tWe examined the expression of the major H 2 S-producing enzymes, cystathionine-b-synthase (CBS) and cystathionine-c-lyase (CSE). CBS was ubiquitously distributed in the mouse pancreas, but CSE was found only in the exocrine. Freshly isolated islets expressed CBS, while CSE was faint. However, high glucose increased the CSE expression in the beta-cells. L-Cysteine or NaHS suppressed islet cell apoptosis with high glucose, and increased glutathione content in MIN6 beta-cells. Pretreatment with L-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
92
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(98 citation statements)
references
References 17 publications
6
92
0
Order By: Relevance
“…We also found that CSE and CBS mRNAs are expressed in mouse pancreatic islets (18,19). Further analyses revealed that expression of CSE, but not CBS, dramatically increases in the islets following glucose stimulation (19). This finding was the first to indicate that expression of H 2 S-producing enzymes can be induced by a physiological stimulus.…”
Section: Production Of H 2 S In Pancreatic β-Cellssupporting
confidence: 54%
See 3 more Smart Citations
“…We also found that CSE and CBS mRNAs are expressed in mouse pancreatic islets (18,19). Further analyses revealed that expression of CSE, but not CBS, dramatically increases in the islets following glucose stimulation (19). This finding was the first to indicate that expression of H 2 S-producing enzymes can be induced by a physiological stimulus.…”
Section: Production Of H 2 S In Pancreatic β-Cellssupporting
confidence: 54%
“…We measured H 2 S content as acid-labile sulfur in the mouse insulin-secreting cell line MIN6 (18), and we found that H 2 S levels in this β-cell line were comparable with those in brain homogenates (5, 9 -11). We also found that CSE and CBS mRNAs are expressed in mouse pancreatic islets (18,19). Further analyses revealed that expression of CSE, but not CBS, dramatically increases in the islets following glucose stimulation (19).…”
Section: Production Of H 2 S In Pancreatic β-Cellsmentioning
confidence: 54%
See 2 more Smart Citations
“…38 We observed that % tail DNA significantly increased in hyperglycemia treated 1.1B4 cells, which is similar to observations with RINm5F, INS-1E cells, and isolated mouse islets. [39][40][41][42] Execution of apoptosis was evident from a slight increase in caspase 3/7 activity after 72 h exposure which has also been observed in hyperglycemia treated INS-1 cells and isolated human islets. 43,44 In conclusion, this study has demonstrated multiple effects of glucotoxicity on gene expression and insulin secretory function in 1.1B4 cells, suggesting that this novel human-derived pancreatic β-cell line is useful for further investigations of β-cell dysfunction and its correction with novel therapeutic agents.…”
Section: Discussionmentioning
confidence: 58%